An Intertemporal Model of Saving and Investment - Abel, Andrew B.; Blanchard, Olivier J. (Econometrica, 1983)
[This paper characterizes a market economy with infinitely long-lived consumers, and value-maximizing firms which face costs of adjustment for capital. The temporary equilibrium of this economy is similar to the short-run equilibrium of standard macroeconomic models. Consumption is a function of wealth, investment is related to the value of firms; equilibrium between aggregate demand and aggregate supply is achieved by the endogenous adjustment of the sequence of current and future interest rates. The dynamic behavior of output, consumption, and investment in this economy is the same as in an optimal growth model with adjustment costs. The paper shows this equivalence and then uses it, together with the equivalence of taxes to technological shocks, to study the dynamic effects of fiscal policy.]